2020
DOI: 10.1177/1084822320907393
|View full text |Cite
|
Sign up to set email alerts
|

How Do Relatives Experience Advanced Home Care? A Qualitative Study

Abstract: The provision of around-the-clock care by advanced home care services subjects families and relatives in Germany to significant psychosocial demands. In addition to coping with the serious illness of their family member, they have to compensate for the lack of privacy caused the constant presence of a nurse. Accordingly, they feel ambivalent about caregivers. The qualitative study conducted narrative interviews that addressed the question as to how relatives and families experience home mechanical ventilation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The qualitative component of our study showed that delivering person-centred care is possible but needs respect and understanding about the ventilated individuals and their families. Additionally, in line with other studies [ 23 , 24 , 31 ], we became aware of a challenging psychosocial factor: Due to the continuous presence of a nurse or an assistant, the boundaries between professional care and family become blurred. Therefore, we recommend to deepen psychosocial aspects in further education and to conduct regular supervisions.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The qualitative component of our study showed that delivering person-centred care is possible but needs respect and understanding about the ventilated individuals and their families. Additionally, in line with other studies [ 23 , 24 , 31 ], we became aware of a challenging psychosocial factor: Due to the continuous presence of a nurse or an assistant, the boundaries between professional care and family become blurred. Therefore, we recommend to deepen psychosocial aspects in further education and to conduct regular supervisions.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, ventilated individuals in an SLC are also supported by their family caregivers, e.g., by frequent and time-consuming visits, care coordination, managing finances, shopping or household activities. Other qualitative studies have confirmed a substantial burden to the lives of family caregivers and call for approaches to support them and improve caregiver well-being [ 24 , 30 , 31 ]. To reduce the burden on family caregivers and improve care overall, we recommend care focusing on the family, and not only the ventilated individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation